Shared Spaces and Social Integration - Thalita dos Santos Dalbelo; Adriana B. Dieguez; Aline Eid Galante; Gabriela M. Romero; Talita M. Torniziello (Journal of Sustainability Perspectives, 2022)
The pandemic caused by the SARS-COv2 virus demanded actions in universities to ensure safety public health of their community. Several fronts are working in this direction, from physical distancing and sanitation protocols, to the use of indoor and outdoor environments, which includes the circulation of pedestrians and cyclists through the campuses. The University of Campinas is carrying out a tactical urbanism project, consisting of a set of actions aimed at low-cost changes in the built environment to test possible improvements through a living laboratory that involves the entire local community. The living laboratory is an innovative systemic approach that enables the integration of research and innovation in a territorial context through co-creation that involves the local community. The objective of the living laboratory of tactical urbanism at Unicamp is to encourage and guide the circulation of pedestrians and cyclists on the campuses in conditions that ensure physical distance. For this, workshops, questionnaires, decisions and collaborative actions are carrying out, so the community is involved in all stages of the project. After the situational survey and planning, actions should involve surface design with patterns and artistic paintings along the streets in order to promote shared use between modes of transport with special consideration for pedestrians and cyclists. As a result, it is expected that Unicamp will be able to restart face-to-face activities during the pandemic with public safety, mobility and low investment.Keyword: Sustainable Urban Mobility, Pedestrian, Cyclist, Sustainable Campus